2019
DOI: 10.1038/s41598-019-45239-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trait anxiety on attentional mechanisms in combined context and cue conditioning and extinction learning

Abstract: Sensory processing and attention allocation are shaped by threat, but the role of trait-anxiety in sensory processing as a function of threat predictability remains incompletely understood. Therefore, we measured steady-state visual evoked potentials (ssVEPs) as an index of sensory processing of predictable and unpredictable threat cues in 29 low (LA) and 29 high (HA) trait-anxious participants during a modified NPU-paradigm followed by an extinction phase. Three different contextual cues indicated safety (N),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 71 publications
4
16
0
Order By: Relevance
“…Crucial for the later generalization test, successful fear conditioning was indexed in both ssVEP amplitude and arousal, valence and US expectancy ratings during acquisition, and social anxiety was not associated with stronger discrimination between conditioned stimuli or generally increased ratings. Thus, the CS+ during acquisition elicited increased visuocortical responses reflecting enhanced sensory engagement (Stegmann et al, 2019a;Wieser et al, 2014c). However, during habituation and acquisition, subjects with higher social anxiety showed overall amplified visuocortical responses to the face stimuli, which is in line with the notion of generally heightened sensitivity to facial expressions in social anxiety disorder (McTeague et al, 2018) and has been observed previously in Bayes factors of main and interaction effect models (M 1 -M 3 ) compared to the 'random intercept only' model (Null model) for the lateral inhibition pattern (weights: +2,-2, +0.5, +1, +0.5,-2 for CS+, GS1, GS2, GS3, GS4, CS-), quadratic trend (weights: +2.5334, +1.0934,-0.0267, À0.8267,-1.3067, À1.4667) and linear trend (weights: +2.5, +1.5, +0.5,-0.5, À1.5,-2.5).…”
Section: Discussionmentioning
confidence: 96%
“…Crucial for the later generalization test, successful fear conditioning was indexed in both ssVEP amplitude and arousal, valence and US expectancy ratings during acquisition, and social anxiety was not associated with stronger discrimination between conditioned stimuli or generally increased ratings. Thus, the CS+ during acquisition elicited increased visuocortical responses reflecting enhanced sensory engagement (Stegmann et al, 2019a;Wieser et al, 2014c). However, during habituation and acquisition, subjects with higher social anxiety showed overall amplified visuocortical responses to the face stimuli, which is in line with the notion of generally heightened sensitivity to facial expressions in social anxiety disorder (McTeague et al, 2018) and has been observed previously in Bayes factors of main and interaction effect models (M 1 -M 3 ) compared to the 'random intercept only' model (Null model) for the lateral inhibition pattern (weights: +2,-2, +0.5, +1, +0.5,-2 for CS+, GS1, GS2, GS3, GS4, CS-), quadratic trend (weights: +2.5334, +1.0934,-0.0267, À0.8267,-1.3067, À1.4667) and linear trend (weights: +2.5, +1.5, +0.5,-0.5, À1.5,-2.5).…”
Section: Discussionmentioning
confidence: 96%
“…Mirroring the organization of visual receptive fields, threat-related sensory amplification has been reported for visual stimuli differing in orientation 10,11 , spatial frequency 12 , location 13 , and color 14 . However, enhanced visuocortical responses have also been observed for more complex visual stimuli, like geometric symbols 15,16 , pictures of virtual rooms 17 and facial identities 18,19 .…”
mentioning
confidence: 99%
“…Alterations in threat-safety learning have been reported across clinical samples. 8,29,30,72 Recently, we reported altered neural signatures in youth with chronic pain (eg, amygdala, hippocampus, and medial prefrontal cortex) during extinction of a learned threat, 34 specifically in patients with elevated catastrophizing.…”
Section: Introductionmentioning
confidence: 99%